Freedom is not free: Manager disloyalty and bank debt reliance - Bu, Luofan; Ng, Jeffrey; Song, Byron Y.; Yan, Mark Yuzhi (Journal of Corporate Finance, 2026)
Traditionally, fiduciaries' duty of loyalty requires them not to pursue business opportunities that could benefit their own companies. However, starting with Delaware in 2000, several states began allowing companies to waive this duty. We find that the debt structure of firms in waiver-adopting states shifts from public debt to bank debt, suggesting that these firms rely on more intense bank monitoring to address potential managerial disloyalty. The shift is more pronounced for firms with CEOs who are more likely to appropriate business opportunities and less pronounced for firms with stronger shareholder monitoring. We also find that bank debt mitigates the adverse effect of corporate opportunity waivers on shareholder wealth, the stock market reacts positively to the bank debt issuances of firms affected by these waivers, and corporate opportunity waiver laws increase the total debt market funding costs for affected firms. Collectively, our paper provides novel evidence that firms seek creditor governance to mitigate the loss of internal governance resulting from changes in the legal environment.